Natural sunscreen formulation with a high sun protection factor (SPF) from tengkawang butter and lignin - Darmawan, Muhammad Arif; Ramadhani, Nurul Hikmah; Hubeis, Nadhira Alifa; Ramadhan, Muhammad Yusuf Arya; Sahlan, Muhammad; Abd Aziz, Suraini; Gozan, Misri (Elsevier, 2022)
Sun protection agents from natural materials have a lower risk of side effects. This study evaluated the effect of lignosulfonate addition to increase the quality and SPF value of tengkawang butter. The sunscreen formulation is made with a mixture of tengkawang butter as the primary ingredient of sunscreen and lignosulfonate as a natural activating agent. Variations in lignosulfonate types (Ca-Lignosulfonate, Mg-Lignosulfonate, and Na-Lignosulfonate) and concentration (1%, 2.5%, 5%, and 10% w/w) were used in this study. The results show the addition of Ca, Mg, and Na-lignosulfonate has reduced the acidity of tengkawang butter from 4.795 ± 0.125 mg NaOH/g sample to 3.28 ± 0.13, 3.18 ± 0.28, and 2.39 ± 0.28 mg NaOH/g sample, respectively. The peroxide number of tengkawang butter was also reduced with the addition of Ca, Mg, and Na-lignosulfonate from 3.68 ± 0.73 meq O2/kg sample to 3.59 ± 0.62, 3.62 ± 0.67 and, 3.59 ± 0.52 meq O2 /kg sample, respectively. The results showed that adding 10% (w/w) Ca-lignosulfonate, Mg-lignosulfonate and Na-lignosulfonate increased the SPF value of tengkawang butter from 4.04 ± 0.12–13.12 ± 0.26 (224%), 13.05 ± 0.11 (223%), and 16.98 ± 0.95 (320%), respectively. The increase of SPF value has a relationship with the chromophore compounds in lignin. The results of this study can be used as a cosmetic formulation with high SPF to protect the skin from ultraviolet rays.